Determinants of Trust in BAZNAS and Implications for Interest in Paying Zakat - Kinanti, Mutiara; Putra, Wirmie Eka; Mansur, Fitrini (Jurnal Ar-Ribh, 2025)
This research aims tois to determine the impact of accountability and transparency on trust in amil zakat institutions and its implications for muzak interest in paying zakat in BAZNAS Jambi City. The respondents are 100 muzak who pay zakat in BAZNAS Jambi City.  The results show that the variable accountability has a significant effect on trust in Amil Zakat Agency with a p-value of 0.000 0.05.  Transparency variable has significant effect on trust in Amil Zakat Agency with p-value 0.002 0.05. Variable accountabilityhas no effect on the interest of Muzakki towards Zakat payment with p value 0.286 0.05.  The variable transparency has no effect on the interest of muzak towards paying zakat with p-statistic value 0.150 0.05. The variable accountability has a significant effect on muzak's interest in zakat payment mediated by trust in Amil zakat agencies with p-value 0.000 0.05. The transparency variable has a significant effect on muzak interest in zakat payment mediated by trust in amil zakat institutions, with a p-value of 0.0018 0.05.